The Cell Envelope Integrity Protein Homologue D0Y85_RS06240 of Stenotrophomonas Confers Multiantibiotic Resistance - Chuanqing Zhong; Xiaoqiang Deng; Aihua Jiang; Yayu Liu; Yuanyuan Liu; Jiafang Fu; Guangxiang Cao (Canadian Journal of Infectious Diseases and Medical Microbiology, 2024)
Background. The potential role of cell envelope integrity proteins in mediating antibiotic resistance is not well understood. In this study, we investigated whether the cell envelope integrity protein D0Y85_RS06240 from the multiantibiotic resistant strain Stenotrophomonas sp. G4 mediates antibiotic resistance. Methods. Bioinformatics analysis was conducted to identify proteins related to the D0Y85_RS06240 protein. The D0Y85_RS06240 gene was heterologously expressed in Escherichia coli, both antibiotic MICs and the effect of efflux pump inhibitors on antibiotic MICs were determined by the broth microdilution method. A combination of antibiotic and efflux pump inhibitor was used to investigate bacterial killing kinetics, and binding of D0Y85_RS06240 to antibiotic molecules was predicted by molecular docking analysis. Results. Sequence homology analysis revealed that D0Y85_RS06240 was related to cell envelope integrity proteins. The D0Y85_RS06240 heterologous expression strains were resistant to multiple antibiotics, including colistin, tetracycline, and cefixime. However, the efflux pump inhibitor N-methylpyrrolidone (NMP) reduced the antibiotic MICs of the D0Y85_RS06240 heterologous expression strain, and bacterial killing kinetics revealed that NMP enhanced the bactericidal rate of tetracycline to the drug-resistant bacteria. Molecular docking analysis indicated that D0Y85_RS06240 could bind colistin, tetracycline, and cefixime. Conclusion. The cell envelope integrity protein D0Y85_RS06240 in Stenotrophomonas sp. G4 mediates multiantibiotic resistance. This study lays the foundation for an in-depth analysis of D0Y85_RS06240-mediated antibiotic resistance mechanisms and the use of D0Y85_RS06240 as a target for the treatment of multiantibiotic-resistant bacterial infections.